Cholinergic modulation of preattentive auditory processing in aging - Pekkonen, Eero; Jääskeläinen, Iiro P.; Kaakkola, Seppo; Ahveninen, Jyrki (NeuroImage (Orlando, Fla.), 2005)
Auditory event-related potential (ERP) components P50 and N100 are thought to index preattentive auditory processing underlying stimulus detection, whereas a subsequent component termed mismatch negativity (MMN) has been proposed to reflect comparison of incoming stimuli to a short-lived sensory memory trace of preceding sounds. Existing evidence suggests impairment of preattentive auditory processing in aging, which appears to be accompanied by decline of cholinergic activity. Previous studies indicate that scopolamine, which is a centrally acting muscarinic receptor antagonist, modulates preattentive auditory processing in young subjects. It has remained elusive, however, to which extent scopolamine affects preattentive auditory processing in aged subjects. We measured auditory responses simultaneously with electroencephalogram (EEG) and magnetoencephalogram (MEG) from nine non-demented elderly subjects after intravenous injection of scopolamine or glycopyrrolate, the latter being a peripherally acting cholinergic antagonist, using a double blind protocol. Scopolamine significantly delayed electric P50, both electric and magnetic N100 responses, whereas subsequent MMN and P200 responses were not altered by scopolamine. Our results indicate that the cholinergic system modulates auditory processing underlying stimulus detection in aging. In addition, auditory evoked responses appear to have different age-related sensitivity to cholinergic modulation. The combined MEG/EEG measurements using particularly auditory N100 response might offer an objective tool to monitor cholinergic activity in aging and Alzheimer's disease (AD).